Syntheses, Characterization, and Crystal Structures of Schiff Base Zinc(II) Complexes With Tetrahedral Coordination. Issue 12 (1st December 2016) - Qin, Jie; Xia, Zhinan; Zhang, Yu; Niu, Fang; You, Zhonglu; Zhu, Hai-Liang
Abstract : Two new mononuclear Schiff base zinc(II) complexes, [ZnClL 1 (N3 )]·2MeOH (1 ) and [ZnBr2 (L 2 )]·MeOH (2 ) (L 1 = 4-methyl-2-[(2-piperazinium-1-ylethylimino)methyl]phenolate; L 2 = 2-[(2-diethylammonioethylimino)methyl]-4-methylphenolate), have been prepared and characterized by elemental analyses, infrared and UV-vis spectroscopy, and single-cyrstal X-ray diffraction. Complex1 crystallizes in the orthorhombic space group Pbca with unit cell dimensions a = 18.703(1), b = 11.8643(6), c = 19.081(1) Å, V = 4234.0(4) Å 3, Z = 8, R 1 = 0.0475, and wR 2 = 0.1046. Complex2 crystallizes in the orthorhombic space group P 21 21 21 with unit cell dimensions a = 8.863(2), b = 13.360(2), c = 17.066(3) Å, V = 2020.7(7) Å 3, Z = 4, R 1 = 0.0803, and wR 2 = 0.1859. The Zn atoms in the complexes are four-coordinated in tetrahedral geometry by the phenolate O and imine N atoms of the Schiff base ligands, and two halide or pseudohalide ligands. Crystals of the complexes are stabilized by hydrogen bonds.